2006
DOI: 10.1007/s11556-006-0004-8
|View full text |Cite
|
Sign up to set email alerts
|

Disability and physical activity in late life—research models and approaches

Abstract: Prevention of disability in late life has become a major public health concern, a key area of ageing research, and also an important target for the development of effective interventions. The increase in life expectancy and the resulting growth of the elderly population are also thought to be driving up the number of elderly people with disabilities. Despite the message that regular moderate physical activity has substantial health benefits even in very old age, older people remain largely sedentary. The most … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0
4

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 39 publications
1
22
0
4
Order By: Relevance
“…Understanding the processes underlying the effects of physical activity on the sense of psychophysical wellbeing in the oldest elderly can help promote active ageing by also meeting the needs of institutionalised older people, who see independence in daily life as a crucial factor [42] but who also wish to participate in activities that are rich in meaning [43,18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Understanding the processes underlying the effects of physical activity on the sense of psychophysical wellbeing in the oldest elderly can help promote active ageing by also meeting the needs of institutionalised older people, who see independence in daily life as a crucial factor [42] but who also wish to participate in activities that are rich in meaning [43,18].…”
Section: Discussionmentioning
confidence: 99%
“…[16] showed that an increase in physical activity is related to an enhanced sense of self-efficacy, which in its turn is associated with an increase in physical performance. Keysor [17] and Heikkinen [18] found that self-efficacy is a mediator in the relationship between physical activity and functional limitations. From what we know, other psychological characteristics apart from self-efficacy were hardly ever considered.…”
Section: Introductionmentioning
confidence: 99%
“…age in healthy individuals [22]. Any additional factor including musculoskeletal pain which negatively impacts on the physical activity level of this group may have adverse consequences for overall health.…”
Section: Main Findingsmentioning
confidence: 99%
“…Furthermore, individuals have different abilities for adaptation in the changing situations, and they differ in the capability to select among different activities, optimize resources, and to use compensatory means so as to be able to carry out the most important activities [34]. When age-related decline in repertoire (health and functioning) threatens the individual's capability to attain important goals, it is possible to improve the disturbed balance between repertoire, personal goals, and environment by e.g., rehabilitating functioning, changing goals, and improving the social and physical environment [35].…”
Section: Future Challengesmentioning
confidence: 99%